The Influence of Perceived Organizational Support and Generation on Employee Engagement - Ida Apriani; Nefi Darmayanti; Patisina (Jurnal Multidisiplin Madani, 2023)
This study aims to determine the effect of Perceived Organizational Support (POS) and Generational Groups on Employee Engagement using the Focus Group Discussion (FGD) intervention method on the POS variable. This research was conducted at a government agency in Aceh. The population is 126 people. For research subjects or FGD participants, there are seven people. The research method used a quasi-experimental with one treatment and a post-treatment group. The hypothesis is designed based on the theoretical framework and research concept. Based on the results of data analysis, it is known that there is a significant influence of POS on employee engagement, referring to the results of the Wilcoxon test with a coefficient of Z: -2.371 and p <0.05 or an Asymp Sig value of 0.018 <0.05. This is consistent with the existing theory that POS affects employee engagement. However, employee engagement is more to the job than to the organization, which is still relatively low. The group dynamics during the FGD were quite visible; participants exchanged different opinions and perceptions about POS to provide new insights leading to changes in views and perceptions about POS, which would affect employee engagement. Meanwhile, the generation found no effect on employee engagement based on the Chi-Square statistical test with an Asymp Sig value of 0.292 > 0.05. This may be due to the limitations of the research subjects. During the FGD process, the participants provided positive input for increasing organizational support for employees, which they believed would later impact increasing employee engagement